Improving oral health‐related quality of life for a traumatic brain injury patient: A case report. (26th September 2019) - Takeuchi, Sawako; Planerova, Adela; Malmstrom, Hans; Saunders, Ralph
Abstract: Aims: A preliminary aim was to determine if a patient who had suffered a traumatic brain injury (TBI) could tolerate removal of his remaining teeth and replacement with partially implant‐supported prosthetic replacements. The primary aim was to determine if the patient and also his main caregiver could assess a potential change in his oral health‐related quality of life. Methods and results: Procedures for the patient were conservative dental restorations, removal of nonrestorable teeth, placement of implants, and fabrication of new dentures. The patient and his primary caregiver, independently, completed the Oral Health Impact Profile‐14 (OHIP‐14) before and after placement of the implants and Locators. The scores were then compared. The results were that both successfully completed the OHIP‐14 and scores showed improvement at 3 and 6 months. Conclusion: This is the first report of both, a TBI patient and his primary caregiver independently self‐assessing improvement in his quality of life using the OHIP‐14 after fabrication of an implant‐supported overdenture.